2020
DOI: 10.1530/joe-19-0561
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroid hormones differentially regulate CYP2D in female wild-type and CYP2D6-humanized mice

Abstract: The CYP2D subfamily catalyses the metabolism of about 25% of prescribed drugs, including the majority of antidepressants and antipsychotics. At present, the mechanism of hepatic CYP2D regulation remains largely unknown. This study investigated the role of sex steroid hormones in CYP2D regulation. For this purpose, Cyp2d22 expression was assessed in the distinct phases of the estrous cycle of normocyclic C57BL/6J (WT) female mice. Cyp2d22 was also evaluated in ovariectomised WT and CYP2D6-humanized (hCYP2D6) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
10
1
Order By: Relevance
“…In contrast to the present findings related to the induction of CYP3A14/25 by OLE, previous in vitro studies indicated that OLE and its metabolite hydroxytyrosol, inactivated androstenedione 6beta-hydroxylase (CYP3A4dependent) activity in microsomal preparations of human liver (Stupans et al, 2001;Stupans et al, 2000;Zhou et al, 2007). This discrepancy could be explained primarily, on the basis of a species-specific regulation of the main CYPs (Konstandi et al, 2020;Visioli et al, 2002a) and the different experimental approaches followed in these studies. Current in vivo study evaluated the OLE effect on CYP3A14/25 in mouse liver microsomes, whereas the in vitro studies mentioned above used human liver microsomes (Stupans et al, 2001;Stupans et al, 2000).…”
Section: Https://wwwfdagov/drugs/drug-interactions-labeling/drug-development-and-druginteractions-table-substrates-inhibitors-and-inducercontrasting
confidence: 96%
See 2 more Smart Citations
“…In contrast to the present findings related to the induction of CYP3A14/25 by OLE, previous in vitro studies indicated that OLE and its metabolite hydroxytyrosol, inactivated androstenedione 6beta-hydroxylase (CYP3A4dependent) activity in microsomal preparations of human liver (Stupans et al, 2001;Stupans et al, 2000;Zhou et al, 2007). This discrepancy could be explained primarily, on the basis of a species-specific regulation of the main CYPs (Konstandi et al, 2020;Visioli et al, 2002a) and the different experimental approaches followed in these studies. Current in vivo study evaluated the OLE effect on CYP3A14/25 in mouse liver microsomes, whereas the in vitro studies mentioned above used human liver microsomes (Stupans et al, 2001;Stupans et al, 2000).…”
Section: Https://wwwfdagov/drugs/drug-interactions-labeling/drug-development-and-druginteractions-table-substrates-inhibitors-and-inducercontrasting
confidence: 96%
“…Hnf4a, encoding a nuclear transcription factor, which holds a determinant role in the regulation of several CYP genes (Daskalopoulos et al, 2012a;Konstandi et al, 2020), was also upregulated by OLE in the liver of mice (Malliou et al, 2018), (Supplemental Fig. 1).…”
Section: Assessment Of Ole Effect On Transcription Factors and Signal Transduction Pathways Related To Cyp Regulationmentioning
confidence: 97%
See 1 more Smart Citation
“…The clinical relevance of this sex difference in CYP2D6 activity is probably small (Aichhorn et al, 2005), as individual differences largely depend on highly variable genetic variations in the CYP2D6 gene (Labbé et al, 2000). Sex differences may, therefore, only become apparent when female sex hormones reach significant heights (Gaedigk, Dinh, Jeong, Prasad, & Leeder, 2018; Konstandi, Andriopoulou, Cheng, & Gonzalez, 2020), for example in pregnancy.…”
Section: Sex Differences In the Pharmacokinetics Of Antipsychoticsmentioning
confidence: 99%
“…External modifying factors such as stress stimuli, diet, environmental chemicals, toxicants and drugs, as well as infectious diseases can also modify the outcome and toxicity of pharmacotherapy by influencing the pharmacokinetic and pharmacodynamic profile of drugs (Zhou et al, 2009 ; Konstandi et al, 2014 ; Thummel and Lin, 2014 ; Roughead, 2015 ). This is attributed to the fact that they can affect the absorption, distribution, metabolism, elimination and activity of drugs (Zhou et al, 2009 ; Konstandi, 2013 ; Konstandi et al, 2013 , 2014 , 2020 ). In this context, stress plays a central role in the multi-factorial regulation of drugs in the body and in determining a drug's pharmacokinetic profile, as it regulates various enzymes that catalyze the metabolism of the majority of prescribed drugs (Konstandi et al, 2000 , 2004 , 2005 , 2008 , 2014 ; Daskalopoulos et al, 2012 ; Konstandi, 2013 ).…”
Section: Introductionmentioning
confidence: 99%